THE ELDERS' SELF CARE AS A WORK INSTRUMENT IN THE CARING PROCESS - Maria Helena Lenardt (Cogitare Enfermagem, 2005)
:An ethnographic study about the elders’self-care in a surgical unit and at their homes. Field data werecollected fromAugust/2002 until March/2003, founded onSpradley’s participant observation and ethnographicinterview. The aim of this study was to get to know howelderly surgical patients deliver self-care during thehospitalization in a surgical unit and at home after discharge.There were (5) identified domains.The theme evolved fromthe ethnographic description was: the elders’ self-care, themeaning cobwebs that they weaved.